What I didn’t grow up with is dangerous: personal experience with a new technology or societal change reduces the belief that it corrupts youth - Protzko, John; Schooler, Jonathan W. (Frontiers in Psychology, 2023)
Introduction Throughout history, technological and societal changes consistently receive suspicion. Their influences appear damaging, corrupting, and potential precursors to societal downfall, with today’s youth often portrayed as the primary victims. This study aims to explore an underlying reason for these perceptions and to investigate why society frequently perceives technological and societal transitions as detrimental to the younger generation. Methods We conduct two studies across a total of 1,702 participants. In a pilot study, American adults generate a list of technological/societal innovations they believe to be especially problematic for youth in various ways. The second study maps beliefs that specific technological/societal shifts are corruptive, correlating with whether American adults experience them during their upbringing. Results People view recent technologies as particularly corrupting of today’s youth. A notable within-person correlation exists between an individual’s exposure to specific technologies during their youth and their belief that these technologies corrupt today’s youth. Specifically, people are more inclined to view technological/societal shifts as corruptive if they don’t experience them during their formative years (b = −0.09, p < 0.001, 95%CI = [−0.11, −0.09]). When reminded of their own exposure to a particular innovation during their upbringing, however, this relationship reduces. Discussion These findings suggest unfamiliarity currently stands as a pivotal factor in societal apprehensions regarding new technological and societal evolutions. As society welcomes new innovations, an enduring cycle emerges where those unacquainted changes seem corruptive to the newer generations. Recognizing this bias, primarily driven by mere unfamiliarity, may be crucial for more balanced evaluations of the inevitable technological and societal progress.